posted by SO LOST .
wanted to know if I got the correct answer?
do you mean something like this: [2(a^10)(b^2)][3(a^2)(b^2)]
if so, then
for constants, we just multiply them normally,, for the variables, recall some laws of exponent,, multiplying terms of same base is also equal to base raised to sum of its exponents,, for example
5^2 * 5^5 = 5^(2+5) = 5^7
x^3 * x^(-4) = x^(3-4) = x^(-1)
for constants: 2*3 = 6
for base a: a^10 * a^2 = a^12
for base b: b^2 * b^2 = b^4
multiplying all of them, we have
hope this helps~ :)
one number is 5times anotherand their sum is 438.whatare the number?give answer in part a,b and c